Peralihan Hak Atas Tanah Melalui Jual Beli Berdasarkan Hukum Adat - I Made Krishna Dharma Kusuma; Putu Gede Seputra; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Humans cannot be separated from the name of land, because land is the one who revives humans and living creatures around it in the progress of the current era of land has Economic Value. Land is the main and largest capital of Indonesia, land is the only capital. The problems of this study are 1) what are the procedures for the transfer of Land Rights according to Customary Law? 2) How is the power of the Law of Sale and Purchase of Property Rights on Land according to Customary Law? The research method used is a normative legal research method, with a literature study of primary and secondary legal materials. The results of the study can be concluded that: 1) the transfer of rights to land according to customary law is valid if the act of light and cash is carried out. The purpose of the sale and purchase agreement is in the presence of PPAT (Land Deed Official) and Witnesses in the transfer of rights to the land and the witness is the head of the village and the local community, which in cash means that there are two actions which are carried out simultaneously, namely the transfer of rights from the seller to the buyer and payment of prices in part or in full from the buyer to the seller. 2). The act of buying and selling that has a good intention is seen when the parties that make a sale and purchase of land rights ask to be done before the Customary Chief / local Village Chief. In the Civil Code the legal protection of buyers with good intentions, if the sale and purchase agreement is carried out based on Customary Law has been protected by the provisions of article 1338 paragraph (3) of the Civil Code.